2019
DOI: 10.1530/biosciprocs.9.009
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis and Sertoli cell numbers and function in rams and bulls

Abstract: The two main types or cellular associations (type I. 2 generations of spermatocytes + 1 of spermatids, type II, 1 of spermatocytes and 2 of spermatids) occupy. respectively, more than half and about a third of the seminiferous epitheliurn cycle in rams and bulls. However, the duration of the cycle of the seminiferous epithelium and that of spermatogenesis differ between the species. A, spermatogonia and Sertoli cell total numbers are highly correlated in adult rams and bulls. Mitosis in Sertoli cells occurs mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Previous studies have shown that larger testicular size in the bull calf, as a consequence of improved calfhood nutrition, is consistent with advanced morphological ontogenesis in the form of greater seminiferous tubule development as well as greater Sertoli cell number and spermatogenic capacity ( English et al, 2018b ). This is important as Sertoli cell number does not increase after puberty in bulls, between birth and puberty, there is an approximate 5-fold increase in the number of Sertoli cells but after that there are no seasonal- or age-related increases in the number of adult Sertoli cells ( Hochereau-de Reviers et al, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that larger testicular size in the bull calf, as a consequence of improved calfhood nutrition, is consistent with advanced morphological ontogenesis in the form of greater seminiferous tubule development as well as greater Sertoli cell number and spermatogenic capacity ( English et al, 2018b ). This is important as Sertoli cell number does not increase after puberty in bulls, between birth and puberty, there is an approximate 5-fold increase in the number of Sertoli cells but after that there are no seasonal- or age-related increases in the number of adult Sertoli cells ( Hochereau-de Reviers et al, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…This induces production of viable spermatozoa and results in an increase in sexual behaviors (libido, aggressiveness, etc.) [6,7]. By the beginning of the breeding season (late August to September in the northern hemisphere), resumption of testicular activity and increased concentration of reproductive hormones (GnRH, LH, FSH and Testosterone) are expected [8][9][10].…”
Section: Reproductive Seasonality and Pubertymentioning
confidence: 99%
“…Therefore, a proportion of the A 1 spermatogonia divide to renew the population of A 1 spermatogonia and the remainder divides into A 2 spermatogonia which engage in the spermatogenetic process. Moreover, Kramer (1960) and Amann (1962b) propose a model of asynchronous spermatogonial generations (Figure 5c) which is not shared by Ortavant (1959) and Hochereau-de Reviers (1970, 1971 and Hochereau-de Reviers et al (1987) (Table 1).…”
Section: Staub and Johnsonmentioning
confidence: 99%